The role of macrophage inhibitory factor in TAA-induced liver fibrosis in mice: modulatory effects of betaine - Radosavljevic, Tatjana; Vukicevic, Dusan; Djuretić, Jasmina; Gopcevic, Kristina; Labudovic Borovic, Milica; Stankovic, Sanja; Samardzic, Janko; Radosavljevic, Milica; Vucevic, Danijela; Jakovljevic, Vladimir (Biomedicines, 2024)
Macrophage inhibitory factor (MIF) is a multipotent cytokine, involved in the inflammatory response to infections or injuries. This study investigates the role of MIF in liver fibrosis and the modulating effect of betaine on MIF in thioacetamide (TAA)-induced liver fibrosis. The wild-type and knockout MIF−/− C57BL/6 mice were divided into the following groups: control; Bet group, which received betaine; MIF−/−; MIF−/−+Bet; TAA group, which received TAA; TAA+Bet; MIF−/−+TAA; and MIF−/−+TAA+Bet group. After eight weeks of treatment, liver tissue was collected for further analysis. The results revealed that TAA-treated MIF-deficient mice had elevated levels of hepatic TGF-β1 and PDGF-BB, as well as MMP-2, MMP-9, and TIMP-1 compared to TAA-treated wild-type mice. However, the administration of betaine to TAA-treated MIF-deficient mice reduced hepatic TGF-β1 and PDGF-BB levels and also the relative activities of MMP-2, MMP-9 and TIMP-1, albeit less effectively than in TAA-treated mice without MIF deficiency. Furthermore, the antifibrogenic effect of MIF was demonstrated by an increase in MMP2/TIMP1 and MMP9/TIMP1 ratios. The changes in the hepatic levels of fibrogenic factors were confirmed by a histological examination of liver tissue. Overall, the dual nature of MIF highlights its involvement in the progression of liver fibrosis. Its prooxidant and proinflammatory effects may exacerbate tissue damage and inflammation initially, but its antifibrogenic activity suggests a potential protective role against fibrosis development. The study showed that betaine modulates the antifibrogenic effects of MIF in TAA-induced liver fibrosis, by decreasing TGF-β1, PDGF-BB, MMP-2, MMP-9, TIMP-1, and the deposition of ECM (Coll1 and Coll3) in the liver.
Gesehen am 22.01.2025